Fintech Acceptance Among MSMEs: A Post-Covid 19 Response - Ulfa Nurhayani; Faisal Rahman Dongoran; Dedy Husrizal Syah; Gaffar Hafiz Sagala (Institute of Research and Community Outreach - Petra Christian University, 2024)
The primary objective of this research is to assess the determinants influencing the adoption of Fintech among MSMEs in Medan City, focusing on MSMEs following the post-pandemic period. This study used an online survey among 156 MSMEs in Medan City. This research uses the Structural Equation Modeling - Partial Least Square (SEM-PLS) approach to analyze the conceptual model, utilizing the SmartPLS version 3 analysis tool. The study's results found that perceived ease of use and subjective norms influence the perceived usefulness of Medan City MSME actors in using Fintech. Overall, the results of this study indicate that perceived ease of use, perceived usefulness, subjective norms, and feeling of safety have a positive and significant effect on the usage of Fintech among MSME actors in Medan City. The results of this study also provide practical implications for using Fintech for MSMEs in Medan City in the new normal era (after the COVID-19 pandemic).